2019
DOI: 10.1101/745174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tagging enhances histochemical and biochemical detection of Ran Binding Protein 9 in vivo and reveals its interaction with Nucleolin

Abstract: AbstractThe lack of tools to reliably detect RanBP9 in vivo has significantly hampered progress in understanding the biological functions of this scaffold protein. We report here the generation of a novel mouse strain, RanBP9-TT, in which the endogenous protein is fused with a double (V5-HA) epitope tag at the C-terminus. We show that the double tag does not interfere with the essential functions of RanBP9. In contrast to RanBP9 constitutive knock-out… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Size of the node reflects size of the term, and color reflects q-value ranging from orange (0.05) to white (0) identified, including 9 previously reported to associate with subunits of the CTLH complex and 76 novel interactors (Figure 3A,B, Supplemental File S4). 17,23,[36][37][38][39] Among those CTLH-associated proteins were the coREST transcriptional repressor complex, ribosomal proteins, heat shock chaperones, lysosomal proteins, RNA binding proteins, proteins associated with desmosomes, and glycolysis enzymes (Figure 3A). GO cellular compartment analysis revealed that the associated proteins were near equally associated with the cytoplasm and nucleus, consistent with the complex being present in both compartments, 15,16 with enrichment as well in extracellular organelles, focal adhesion, and vesicles (Figure 3C).…”
Section: The Endogenous Ranbpm Interactomementioning
confidence: 99%
“…Size of the node reflects size of the term, and color reflects q-value ranging from orange (0.05) to white (0) identified, including 9 previously reported to associate with subunits of the CTLH complex and 76 novel interactors (Figure 3A,B, Supplemental File S4). 17,23,[36][37][38][39] Among those CTLH-associated proteins were the coREST transcriptional repressor complex, ribosomal proteins, heat shock chaperones, lysosomal proteins, RNA binding proteins, proteins associated with desmosomes, and glycolysis enzymes (Figure 3A). GO cellular compartment analysis revealed that the associated proteins were near equally associated with the cytoplasm and nucleus, consistent with the complex being present in both compartments, 15,16 with enrichment as well in extracellular organelles, focal adhesion, and vesicles (Figure 3C).…”
Section: The Endogenous Ranbpm Interactomementioning
confidence: 99%
“…This model has been validated through the use of immunohistochemistry and by coimmunoprecipitation, showing that the expression and interactions of the tagged protein faithfully recapitulates those of the wild type RANBP9. This new murine strain will be instrumental in obtaining data in vivo about the RANBP9immunocoprecipated proteome, without the risk of using antibodies that may recognize RANBP10 [84] .…”
Section: Ranbp10 May Partially Compensate For the Absence Of Ranbp9mentioning
confidence: 99%